評《大乘中觀哲學的生死觀》一文: A Response to "Death and Dying in Chinese Madhyāmika Buddhism" - YIP, Kam Ming (International Journal of Chinese & Comparative Philosophy of Medicine, 2016)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. This article comments on Zhang Ying’s essay “Death and Dying in Chinese Madhyāmika Buddhism”. The central thesis of Zhang’s essay is that Madhyāmika’s non-dualist approach to samsara and nirvana, this world and the other world, and life and death helps narrow the gap between life and death and consequently remove our fear of death, which in turn has important implications for hospice care. However, Zhang did not explain how this non-duality can be put into practice, which is a major defect of Zhang’s paper. And if accessibility to non-duality in practice is not fully explained, people’s confusion around hospice care remains. Moreover, Zhang’s essay fails to explain the implications of Madhyāmika’s non-dualist approach for the practice of hospice care in contemporary society, which Zhang promised to do so. DOWNLOAD HISTORY | This article has been downloaded 147 times in Digital Commons before migrating into this platform.